Aplikasi Statistical Process Control dalam Penjaminan Kualitas Logam Fe, Cr (Iv), Cu dan Zn pada Input Biodigester di 15 Kecamatan di Kabupaten Kebumen - Ida Betanursanti; Alifta Dicasani (Publikasi Indonesia, 2026)
Water quality is a crucial factor in determining the performance and sustainability of the biodigester system. The content of heavy metals in water has the potential to affect the biological process of biogas formation as well as have an impact on environmental health. This study aims to analyze water quality as biodigester inputs based on heavy metal content in 15 sub-districts in Kebumen Regency in order to support the development of biogas as an alternative energy source to support the SDGs program of clean and renewable energy villages. Water sampling was carried out randomly in 15 sub-districts representing mountainous, plain, coastal, and urban areas. Heavy metal concentration measurements were carried out at the UPTD Environmental Laboratory of the Kebumen Regency Environment, Marine and Fisheries Office. The parameters analyzed included levels of chromium (Cr) IV, iron (Fe), copper (Cu), and zinc (Zn). Data was analyzed using a statistical process control approach through a statistical control map to evaluate process variations, as well as process capability analysis using Pp and Ppk indices to assess the ability of water sources to meet the quality standard specification limit as a biodigester input. The results of the study show that there is a variation in heavy metal content between sub-districts. Toxic chromium concentrations with a value of ? 0.67 mg/L were identified in five sub-districts, namely Klirong, Petanahan, Buluspesantren, Karanggayam and Kebumen. Copper concentrations close to the limit of 0.02 mg/L which have the potential to inhibit enzyme activity were found in Petanahan and Kebumen Districts. Based on the analysis of process capabilities, one sub-district was categorized as very good, nine sub-districts were acceptable, and four sub-districts were categorized as poor as biodigester input water sources. These results show that the statistical process control approach is able to provide a quantitative evaluation framework for water quality consistency at the regional scale to support the development of renewable energy-based biodigesters.